Levodopa Dose Equivalency in Parkinson's Disease: Updated Systematic Review and Proposals - Jost, Stefanie T.; Kaldenbach, Marie‐Ann; Antonini, Angelo; Martinez‐Martin, Pablo; Timmermann, Lars; Odin, Per; Katzenschlager, Regina; Borgohain, Rupam; Fasano, Alfonso; Stocchi, Fabrizio; Hattori, Nobutaka; Kukkle, Prashanth Lingappa; et al. (Movement disorders, 2023)
Background To compare drug regimens across clinical trials in Parkinson's disease (PD) conversion formulae between antiparkinsonian drugs have been developed. These are reported in relation to levodopa as the benchmark drug in PD pharmacotherapy as ‘levodopa equivalent dose’ (LED). Currently, the LED conversion formulae proposed in 2010 by Tomlinson et al. based on a systematic review are predominantly used. However, new drugs with established and novel mechanisms of action and novel formulations of longstanding drugs have been developed since 2010. Therefore, consensus proposals for updated LED conversion formulae are needed. Objectives To update LED conversion formulae based on a systematic review. Methods The MEDLINE, CENTRAL, and Embase databases were searched from January 2010 to July 2021. Additionally, in a standardized process according to the GRADE grid method, consensus proposals were issued for drugs with scarce data on levodopa dose equivalency. Results The systematic database search yielded 3076 articles of which 682 were eligible for inclusion in the systematic review. Based on these data and the standardized consensus process, we present proposals for LED conversion formulae for a wide range of drugs that are currently available for the pharmacotherapy of PD or are expected to be introduced soon. Conclusions The LED conversion formulae issued in this Position Paper will serve as a research tool to compare the equivalence of antiparkinsonian medication across PD study cohorts and facilitate research on the clinical efficacy of pharmacological and surgical treatments as well as other non‐pharmacological interventions in PD. © 2023 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.